Uji Aktivitas Antioksidan Ekstrak Buah Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl.) Yang Diformulasikan Kedalam Sediaan Masker Gel - Zaelani, Diki; Pratama, Reza; Japar Sodik, Jajang; Hilda Restu, Afria (JURNAL FARMASI GALENIKA, 2024)
This study utilizes the Phaleria macrocarpa fruit (Phaleria macrocarpa (Scheff.) as an active ingredient in gel mask formulation due to its widespread use as a medicinal plant and its antioxidant properties that can inhibit free radicals. The research began with the collection of the fruit from the experimental garden in Lembang-Bandung, identified as Phaleria macrocarpa (Scheff.) Boerl. Extraction was conducted using the maceration method with 96% ethanol for 3x24 hours. Phytochemical screening results indicated the presence of alkaloids, flavonoids, tannins, triterpenoids, and steroids. Antioxidant activity of the gel masks was tested using the DPPH immersion method, resulting in IC50 values of 60.18 ppm, 57.18 ppm, and 54.82 ppm for three different formulations. The pure extract had an IC50 of 45.11 ppm. The gel masks remained stable despite changes in pH and viscosity, with formulation 2 being the most preferred according to the hedonic test. In conclusion, the Phaleria macrocarpa gel mask exhibits effective antioxidant activity and good stability.